Exchange rates, bond yields and the stock market: nonlinear evidence of Indonesia during the COVID-19 period - Prananta, Billy; Alexiou, Constantinos (Emerald, 2023)
Purpose The authors explore the relationship between the exchange rate, bond yield and the stock market as well as the effect of capital market dynamics on the exchange rate before and during the COVID-19 pandemic. Design/methodology/approach The authors employ a non-linear autoregressive distributed lag (NARDL) methodology using daily data of the Indonesian economy over the period 2012–2021. Findings Whilst, over the full sample period, the authors find no cointegration between the exchange rate, the 10-year bond yield and stock market, for the COVID-19 period, evidence of cointegration is present. Furthermore, the results suggest that asymmetric effects are evident both in the short as well as the long run. Originality/value To the best of the authors’ knowledge, this is the first time that the relationship between the exchange rate, bond yield and the stock market as well as the effect of capital market dynamics on the exchange rate before and during the COVID-19 pandemic has been explored in the case of the Indonesian economy.
Keywords: Capital market dynamics; Exchange rate; Asymmetric effect; Bond market; Stock market